Model Simulasi, Amati, dan Kreasi (Siakre) Berbantukan Mesia Pintar Untuk Meningkatkan Minat Belajar Siswa - Ahmad Irfan Barokah (Jurnal Didaktika Pendidikan Dasar, 2020)
The purpose of this study is to describe the use of the Siena-aided Smart Mesia model and to increase students' interest and learning outcomes in the water cycle material in grade 5 students at SD Negeri Purborejo. The method used is the Classroom Action Research (CAR) model which consists of two cycles. The process of collecting data in research is done by observing interests using student interest observation sheets. The results obtained 15 students (71.4%) expressed interest in cycle 1, and in cycle 2 expressed interest in 19 students (90.4%). Based on the data obtained and associated with the performance indicators determined, it was concluded that the use of the Smart Mesia-assisted SiAKre model could increase students' interest and learning outcomes.